QUALITATIVE STUDY OF INPATIENT MANAGEMENT IN IMPROVING SERVICE QUALITY AT RSUD TRIKORA SALAKAN INDONESIA - Andi Khaerul Musyawir (Universitas Islam Negeri Alauddin Makassar, 2021)
Background:The implementation of the management function requires the competence of the head of the room as the main manager in the inpatient room to improve the quality of service in the hospital.Objective:This research aimed to know the management competence of inpatient room heads in improving service quality at Trikora Salakan General Hospital.Method:The research method was descriptive with a qualitative approach, with did a deep interview to head of nursing medical and head of the room in improving the quality of service.Result:The result of the research showed that the management competence of the head of the room at Trikora Salakan Hospital was still not optimal, this was influence by the management competence of the head of the room in making room planning, organizing, implementing, and evaluating so that the head of the room needed to improve and maintain his role as head of the room so that the implementation of management competence in the inpatient room was still carried out by both by management standards.Conclusion: Planning competence, some of the heads of the room who do not know about the hospital development plan, no one arranges planning in the room by looking at the strategic plan of the hospital-based only on the needs of the room